Does casting method matter in filtration membranes? A comparison in performance between doctor blade and slot‐die extruded polymeric membranes. Issue 24 (9th August 2017) - Chede, Sneha; Griffiths, Peter; Escobar, Isabel C.; Harris, Tequila A. L.
ABSTRACT: Scaling up from a laboratory batch process to a continuous manufacturing process can result in unexpected changes in membrane morphology and performance. To understand how processing effects the structure and performance of cellulose acetate filtration membranes, membranes were produced using laboratory‐scale doctor blade and industrial/production‐scale slot die casting. Differences in morphology were seen because of the different casting method. However, filtration performance using bovine albumin serum and lipase showed no significant differences. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45563. Abstract :